PENINGKATAN HASIL BELAJARSISWA PADA PEMBELAJARAN IPS DENGAN MENGGUNAKAN PENDEKATAN KONTRUKTIVIS DI KELAS IV - YANTI, HELLI (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research is begin of truth in primari school. The study to teacher cente. Sd the result of students in social study low. This case because the teacher in this study used the convensional nearly so that cant push the knowledge of students. The purpose of othis research is to descrip the level social study with used the contruktivis nearly in fourth class of primary school. With the sample of research are 22 people. The nearly used in this research is qualitative and quantitative with the hind of research is improved student lerning out comes. This research improved to two syclus that identifich from planning activity, do activity and see and reflection. The sesult of planning studys I can be see from the ability of teachers to design lessens from 62,5% and then II syclus get 85,7%, the activity of teacher 69,3% to 87, 7%. At students activity in syclus I get 67,3% and then syclus II get 86,3%, at the result study syclus I get 72,1% go then syclus II get average 77%. So that can be concluded that social study with contruktivis nearly can improved the result of students study of fourth class at primary school.Keywords:  Kontruktivis, learning outcomes, teaching social stud